Comparison of time-dependent viscosity slurry and cement-clay slurry for anti-seepage grouting on faults - Zhang, Jiaxing; Pei, Xiangjun; He, Zhihao; Pei, Zuan; Zheng, Guoxun (Frontiers in Earth Science, 2023)
The geological conditions of fault zones are complex, with shattered rock mass, fracture development, uneven filling, and connection to aquifers to form the water-conducting channels, all of which weaken the seepage resistance of a stratum. This has led to curtain grouting being used to improve the anti-seepage properties of fault zones. This study evaluates the groutability and impermeability of a time-dependent viscosity slurry and a cement-clay slurry in a shattered fault zone. Rheology, setting time, mechanism, and permeability were tested to evaluate the groutability, and Lugeon and grouting field tests were carried out to evaluate the anti-seepage grouting characteristics of a fault zone. The results show that the time-dependent viscosity slurry had higher initial fluidity, a shorter and more controllable setting time, and higher strength than cement-clay slurry, better ensuring the slurry diffusion radius, pore filling rate, and bearing capacity and durability of the consolidated body. The permeability coefficient of the two grouts was less than 1×10-7cm/s, and the blocking rate of heavy metal ions was more than 98%, sufficient to effectively control the leakage of sewage. The P~Q curve of the Lugeon test showed that the original strata were of the washout type (>200 Lu), and the rock mass quality grade was the D grade (Poor). Under the same grouting depth, the amount of time-dependent viscosity slurry required was 72.6% of that of cement-clay slurry, and the permeability decreased to 10Lu, far lower than the 50Lu of the cement-clay slurry. The time-dependent viscosity slurry improved the quality of the rock mass from D to B-C grade, while the cement-clay slurry test area is remained C-D grade. In general, the time-dependent viscosity slurry performed better than cement-clay slurry in the water-bearing fault zone.